Acute myocarditis. Role of histological and virological examination in the diagnosis and assessment of immunosuppressive treatment. Issue 1 (January 1984) - Daly, K; Richardson, P J; Olsen, E G; Morgan-Capner, P; McSorley, C; Jackson, G; Jewitt, D E
Abstract : Twelve patients, who presented with congestive cardiac failure after a recent influenza like illness, had a clinical diagnosis of acute myocarditis confirmed histologically after endomyocardial biopsy. Eight were under 30 years of age. Serological testing suggested a viral aetiology in six patients. Nine patients were treated with immunosuppressive drugs (prednisolone and azathioprine in seven, prednisolone alone in two). At two months, seven patients showed clinical and haemodynamic improvement (ejection fraction rose from 26.8 to 49% and left ventricular end diastolic pressure fell from 26.4 to 16.2 mm Hg) with biopsy evidence of healed myocarditis. In two, activity persisted. At six months' follow up only four of these patients had maintained their improvement. One patient relapsed after stopping treatment, subsequently improving on its reinstatement. Two patients developed severe interstitial myocardial fibrosis with gradual deterioration. Virology and myocardial histology were complementary in the diagnosis of acute myocarditis in these young patients, whose response to immunosuppressive treatment was variable. An apparent early response could not be clearly separated from variables in the natural history of the condition. Serial endomyocardial biopsies showed a progression to congestive cardiomyopathy in two patients. Multicentre controlled trials will be necessary to assess fully the role of immunosuppressive treatment in this condition.